The musculoskeletal system manifestations in children with familial Mediterranean fever - Ferhat Demir; Leyla Gizem Bolaç; Tuba Merter; Sezin Canbek; Özlem Doğan; Yasemin Kendir Demirkol; Jale Yildiz; Hamdi Levent Doganay; Betul Sozeri (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: Familial Mediterranean fever (FMF) is a monogenic inherited periodic fever syndrome presenting with episodes of self-limiting fever and inflammation of serosal membranes. Besides the findings in the diagnostic criteria, musculoskeletal findings can also be seen in FMF patients attacks. In this study, we aim to reveal the frequency and genotype association of musculoskeletal manifestations in children with FMF. METHODS: The patients diagnosed with FMF between January 1, 2017 and June 1, 2019, and followed for at least six months in our pediatric rheumatology clinic were included in this study. Musculoskeletal manifestations of patients were enrolled. The patients were grouped according to the 'Mediterranean Fever' (MEFV) gene variants. Musculoskeletal manifestations of the patients were compared between the groups. RESULTS: The study group included 634 children with FMF (336 female and 298 male, F/M: 1.13/1). The clinical manifestations of patients in the attack period were as follows: 99% of the patients had a fever, 87.3% had abdominal pain, 20.7% had chest pain, 11.3% had vomiting, 10.7% had erysipelas like erythema, and 9.3% had a headache. The musculoskeletal symptoms were accompanied by 58.6% (n=372) of the patients during the attack period. The most common musculoskeletal manifestation was found as arthralgia (32.6%, n=206). Also, the other musculoskeletal manifestations were as follows during attacks: arthritis in 23.7% (n=150), myalgia in 20.5% (n=130), exertional leg pain in 6.5% (n=41), and protracted febrile myalgia in 1% (n=7) of the patients. It was observed that the musculoskeletal manifestations were significantly higher in patients with homozygous M694V variants in exon-10 (p=0.017). The musculoskeletal manifestations were more common in the attack periods of patients carrying the M694V variant in at least one allele (p=0.019). CONCLUSION: We found that the musculoskeletal manifestations were accompanied in more than half of patients with FMF. M694V variant was found as a risk factor for emerging musculoskeletal manifestations.